Junior High School Students' Critical Thinking Ability in Biology Learning through Liveworksheet E-LKPD Based on Scientific Approach - Abu Bakar Chaniago, Otis Aprillia; Maulina, Dina; Wiono, Wisnu Juli; Hernawati, Diana (Biosfer: Jurnal Tadris Biologi, 2022)
This study aimed to assess junior high school students' critical thinking skills in biology learning using Liveworksheet E-LKPD  based on a scientific approach. Critical thinking skills assessments, teacher interviews, and student response questionnaires were used as data collection techniques. The n-gain, normality test, homogeneity test, and independent sample t-test were used to assess critical thinking skills data. The questionnaire and interview data were analyzed descriptively in percentage form. The results revealed significant differences in critical thinking skills between students in the experimental and control groups (Sig. < 0.05). The learning process and teaching materials employed produce differences in students' critical thinking skills, students are not accustomed to working on critical thinking problems, and teachers have not maximized learning activities with the scientific approach.ABSTRAK: Tujuan penelitian ini adalah untuk mengetahui kemampuan berpikir kritis siswa pada pembelajaran biologi di jenjang SMP melalui pemanfaatan E-LKPD dalam liveworksheet berbasis pendekatan saintifik. Teknik pengumpulan data dilakukan dengan pemberian tes kemampuan berpikir kritis, pelaksanaan wawancara guru, dan angket tanggapan siswa. Data kemampuan berpikir kritis dianalisis dengan n-gain, uji normalitas, uji homogenitas, dan uji independen sampel t-test, sedangkan data angket dan wawancara dianalisis secara deskriptif dalam bentuk persentase. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan berpikir kritis yang nyata di antara siswa kelompok eksperimen dan kelompok kontrol (Sig. < 0,05). Perbedaan kemampuan berpikir kritis siswa disebabkan oleh proses pembelajaran dan bahan ajar yang digunakan serta siswa belum terbiasa mengerjakan soal-soal berpikir kritis dan guru belum mengoptimalkan kegiatan pembelajaran dengan pendekatan saintifik.